Clinical usefulness of a single-use splinting tube for poor endoscope operability in deep colonic endoscopic submucosal dissection - Asayama, Naoki; Oka, Shiro; Tanaka, Shinji; Sumimoto, Kyoku; Hirano, Daiki; Tamaru, Yuzuru; Ninomiya, Yuki; Shigita, Kenjiro; Hayashi, Nana; Nishiyama, Soki; Chayama, Kazuaki (Endoscopy International Open, 2016)
Background and study aims: Poor endoscope operability remains a significant challenge during colorectal endoscopic submucosal dissection (ESD). We retrospectively evaluated the experience and clinical usefulness of a new single-use splinting tube in deep colonic ESD in the setting of poor scope operability. Patients and methods: Among 691 patients with colorectal tumors treated with ESD at Hiroshima University Hospital between November 2009 and July 2015, we analyzed 20 consecutive patients who underwent deep colonic ESD using a single-use splinting tube because of poor scope operability. Poor operability was defined as paradoxical movement of the endoscope, poor control with adhesions, and lesion motion with heartbeat or breathing. Technical and clinical success rates and adverse events were assessed.Results: Paradoxical movement and poor control with adhesions were improved in all cases using the single-use splinting tube. The en bloc resection rate was 95 % (19/20) and histological en bloc resection rate was 100 % (20/20). There were no complications related to use of the splinting tube.Conclusions: Use of a single-use splinting tube helped to overcome poor scope operability in deep colonic ESD.